IsiZulu idiomatic expressions derived from selected biblical figures: a morpho-syntactic & socio-cultural assimilation critique - Sibusiso Percy Khumalo; Sizwe Zwelakhe Dlamini (Cogent Arts & Humanities)
The aim of this article is to analyse IsiZulu idioms that are influenced by biblical figures such as Jonah, Lazarus, Judas Iscariot, Jezebel, and Delilah. This is done by considering how these idioms have been morpho-syntactically and socio-culturally adopted and adapted to the IsiZulu language. The article uses African cultural hermeneutics as a theory and document analysis as a qualitative research technique. The findings demonstrate that IsiZulu idioms, such as ‘ukuphelela esiswini njengoJona’ (to end in a belly like Jonah)’, ukuba nguLazaru’ (to be Lazarus) ‘, ukuba nguJudasi Iskariyothi’ (to be Judas Iscariot) ‘, ukuba nguJezebheli’ (to be Jezebel), and ‘ukuba nguDelila’ (to be Dalila), have been morphologically adapted and used in different IsiZulu sentence forms and tenses. The findings also show that these idioms have been socio-culturally assimilated and used in everyday discourses within the Zulu community.